An Interesting Case of Nonlupus Full-House Nephropathy - Satyanand Sathi; Alok Sharma; Anil Kumar Garg; Virendra Singh Saini; Manoj Kumar Singh; Devinder Vohra; Arvind Trivedi (Case Reports in Nephrology)
Full-house immunofluorescence and endothelial tubuloreticular inclusions are known as characteristic features of lupus nephritis. However, both features are not pathognomonic for lupus nephritis. A kidney biopsy specimen showing full-house immunofluorescence pattern in the absence of autoantibodies and classical clinical features of Systemic Lupus Erythematosus (SLE) is now considered as nonlupus full-house nephropathy (FHN). Nonlupus FHN may be idiopathic or due to other disease processes known as secondary nonlupus FHN. Here, we report the case of a 36-year-old female who presented with nephrotic proteinuria with bland urine sediment. Additional analyses revealed normal serum antinuclear antibody (ANA), normal anti-double-stranded DNA (anti-dsDNA) antibodies, and normal serum C3 and C4 levels. A renal biopsy showed a normal-appearing glomerulus without any proliferation or capillary wall thickening and widespread glomerular immune deposits (full-house effect; IgA, IgG, IgM, C3, and C1Q) on direct immunofluorescence. Renal electron microscopy showed diffuse effacement of visceral epithelial cell foot processes and mesangial electron dense deposits. The patient was diagnosed as nonlupus FHN. There is a controversial role of steroids and other immunosuppressive drugs in the treatment of nonlupus FHN patients, but our case patient responded favourably to steroid therapy. The term nonlupus FHN can be used as an umbrella term for patients who do not satisfy the clinical and serological criteria of SLE.